Application of Pomegranate Peel Extract, a Waste Agricultural Product, as a Natural Preservative in Tahini - Rayeheh Ghasemi; Fateme Akrami Mohajeri; Ali heydari; Seyed Ali Yasini; Arefeh Dehghani Tafti; Elham Khalili Sadrabad (International Journal of Food Science)
The pomegranate peel, an agricultural by-product or waste, is a rich source of bioactive compounds. In the current study, the addition of different concentrations of pomegranate peel hydromethanolic extract (PPE) into tahini was investigated. The hydromethanolic extract of pomegranate peel in the ratio of 1 : 1 was prepared, and the PPE yield was evaluated. The HPLC and Folin-Ciocalteu methods were used to determine phenolic compounds and total phenolic content of PPE, respectively. The antioxidant activity of PPE was investigated by DPPH and FRAPS assays. Then, the different concentration of PPE (0, 0.25, 0.5, 1, and 2%) was added to tahini. Thereafter, peroxide value, TBARS, and sensory analyses were determined during 6 months of storage. The PPE yield was reported at 18.90%. Gallic acid, ellagic acid, and punicalagin were identified as the most abundant phenolic compounds in PPE. The total phenolic content, DPPH, and FRAP antioxidant assay of PPE were evaluated as 1577.65 mg/g GAE, 54 μg/ml, and 483.24 mM, respectively. It was shown that by the addition of PPE in tahini, the increase in peroxide value and TBARS was controlled. The concentrations 1 and 2% act better to inhibit lipid peroxidation. Overall, the general acceptance of samples containing 1 and 2% PPE was recorded better than other samples. The PPE showed a good function as a natural antioxidant in tahini to retard oxidation.